Traditional food and herbal uses of wild plants in the ancient South-Slavic diaspora of Mundimitar/Montemitro (Southern Italy) - di Tizio Alessandro; Łuczaj Łukasz; Quave Cassandra L; Redžić Sulejman; Pieroni Andrea (BMC, 2012)
Abstract Background In Europe, only a limited number of cross-cultural comparative field studies or meta-analyses have been focused on the dynamics through which folk plant knowledge changes over space and time, while a few studies have contributed to the understanding of how plant uses change among newcomers. Nevertheless, ethnic minority groups and/or linguistic "isles" in Southern and Eastern Europe may provide wonderful arenas for understanding the various factors that influence changes in plant uses. Methods A field ethnobotanical study was carried out in Mundimitar (Montemitro in Italian), a village of approx. 450 inhabitants, located in the Molise region of South-Eastern Italy. Mundimitar is a South-Slavic community, composed of the descendants of people who migrated to the area during the first half of the 14th century, probably from the lower Neretva valley (Dalmatia and Herzegovina regions). Eighteen key informants (average age: 63.7) were selected using the snowball sampling technique and participated in in-depth interviews regarding their Traditional Knowledge (TK) of the local flora. Results Although TK on wild plants is eroded in Montemitro among the youngest generations, fifty-seven taxa (including two cultivated species, which were included due to their unusual uses) were quoted by the study participants. Half of the taxa have correspondence in the Croatian and Herzegovinian folk botanical nomenclature, and the other half with South-Italian folk plant names. A remarkable link to the wild vegetable uses recorded in Dalmatia is evident. A comparison of the collected data with the previous ethnobotanical data of the Molise region and of the entire Italian Peninsula pointed out a few uses that have not been recorded in Italy thus far: the culinary use of boiled black bryony (Tamus communis) shoots in sauces and also on pasta; the use of squirting cucumber ( Ecballium elaterium) juice for treating malaria in humans; the aerial parts of the elderberry tree ( Sambucus nigra) for treating erysipelas in pigs; the aerial parts of pellitory ( Parietaria judaica) in decoctions for treating haemorrhoids. Conclusions The fact that half of the most salient species documented in our case study - widely available both in Molise and in Dalmatia and Herzegovina - retain a Slavic name could indicate that they may have also been used in Dalmatia and Herzegovina before the migration took place. However, given the occurrence of several South-Italian plant names and uses, also a remarkable acculturation process affected the Slavic community of Montemitro during these last centuries. Future directions of research should try to simultaneously compare current ethnobotanical knowledge of both migrated communities and their counterparts in the areas of origin.